Numerical Study of the effect of adding cement with bentonite on resistance of pile friction in sandy soils. - خضور, علي; توفيق فياض ,; رامي العبده , (Latakia University Journal -Engineering Sciences Series, 2023)
As a result of the increasing population growth, the populations desire to live in tall buildings with deep foundations increased, where piles are used as deep foundations for engineering constructions. Bentonite is used to stabilize walls of excavations when piling is carried out to prevent the collapse of weak soil sides during excavation, due to its high swelling property. When casting the piles, the bentonite rises to the top due to its low density, which is less than the density of the casting concrete, and the concrete settles to the bottom, and a thin and weakly frictional layer of bentonite remains (filter cake) around the body of the pile, this layer causes the piles frictional bearing capacity to drop to about (30%-10%) according to (Ng, 2002), as a result of the viscosity of bentonite used. Which prompted to do a lot of research on the effect of the viscous layer of bentonite on the performance of the pile on friction. This research deals with conducting a numerical study of the effect of a thin bentonite layer treated with different percentages of cement additives, on the performance of the pile on friction. By placing a numerical model of a vertically loaded pile and perforated with treated bentonite within sandy soil, to obtain the best numerically studied addition ratio of sand that improves the piles resistance to friction, reduces the economic cost of using bentonite, and maintains the workability of bentonite